Weigth Loss in a Neonate- A Case of Hypoaldosteronism - Saevarsson, Ivar; Jonasdottir, Soffia Gudrun; Jonsdottir, Berglind (Laeknabladid, 2023)
The Neonatal weight loss is a common problem which most physicians who take care of newborns should recognise. The most common reason is insufficient dietary intake. However the reason can also be an underlying disease. Aldosterone insufficiency in neonates is a rare disease and if not treated correctly can be life threatening. It presents with serious electrolytes abnormalities and metabolic acidosis. It is therefore important to distinguish between serious and benign causes of weight loss in neonates.